An Examination of the RDoC Negative Valence Systems Domain Constructs and the Self-Reports Unit of Analysis. Issue 6 (November 2022) - Hasratian, Anni M.; Meuret, Alicia E.; Chmielewski, Michael; Ritz, Thomas
Highlights: RDoC is a framework for researchers to study psychopathology independent of the DSM. The need to populate the RDoC matrix further is a high priority. Measures related to the Negative Valence Systems were administered to four samples. Factors reflecting most Negative Valence Systems constructs emerged in all samples. We recommend additional self-reports for the Negative Valence Systems constructs. Abstract: In response to shortcomings with the current diagnostic classification system for mental health disorders, such as poor validity and reliability of categorical diagnoses, the National Institute of Mental Health proposed the Research Domain Criteria (RDoC) initiative to move towards a dimensional approach using translational research. The current study examined associations between measures of behaviors, cognitions, and mental health symptoms and how they overlap in the Negative Valence Systems (NVS) domain. Specifically, we examined how the Self-Reports unit of analysis reflects the RDoC NVS constructs of acute threat, potential threat, sustained threat, frustrative nonreward, and loss. The overall goal was to identify additional self-report measures that reflect these constructs. Participants, two student samples and two community samples (total N  = 1, 509), completed online self-reported measures. Questionnaire total and subscale scores were submitted to a principal-axis factor analysis with Promax rotation separately for each sample. For both student samples and one community sample six-factor solutions emerged reflecting major aspects of the RDoC NVS and positive valence systems, particularly acute threat (i.e., fear/panic), potential threat (i.e., inhibition/worry), sustained threat (i.e., chronic stress), loss (i.e., low well-being), frustrative nonreward (i.e., reactive aggression), and reduced behavioral activation. The second community sample differed in that fear/panic and frustration/anger was combined in a general distress factor. Recommendations for additional NVS self-report markers are discussed.